HDAC 3-selective inhibitor RGFP966 demonstrates anti-inflammatory properties in RAW 264.7 macrophages and mouse precision-cut lung slices by attenuating NF-κB p65 transcriptional activity - Leus, Niek G.J. (Biochem Pharmacol, 2016)
The increasing number of patients suffering from chronic obstructive pulmonary disease (COPD) represents a major and increasing health problem. Therefore, novel therapeutic approaches are needed. Class I HDACs 1, 2 and 3 play key roles in the regulation of inflammatory gene expression with a particular pro-inflammatory role for HDAC 3. HDAC 3 has been reported to be an important player in inflammation by deacetylating NF-κB p65, which has been implicated in the pathology of COPD. Here, we applied the pharmacological HDAC 3-selective inhibitor RGFP966, which attenuated pro-inflammatory gene expression in models for inflammatory lung diseases. Consistent with this, a robust decrease of the transcriptional activity of NF-κB p65 was observed. HDAC 3 inhibition affected neither the acetylation status of NF-κB p65 nor histone H3 or histone H4. This indicates that HDAC 3 inhibition does not inhibit NF-κB p65 transcriptional activity by affecting its deacetylation but rather by inhibiting enzymatic activity of HDAC 3. Taken together, our findings indicate that pharmacological HDAC 3-selective inhibition by inhibitors such as RGFP966 may provide a novel and effective approach toward development of therapeutics for inflammatory lung diseases.